Reasons for Women to Stay in Violent Dating Relationships: Literature Review - Swasti, Ni Kadek Candra; Swandi, Ni Luh Indah Desira; Wulanyani, Ni Made Swasti (Sinergi International Journal of Psychology, 2023)
In reality, dating relationships are not always fill up by positive romantic relationships. There are many deviant dating behaviors that lead to cases of violence. Interestingly, although dating violence clearly has many negative impacts on various aspects, some women decide to stay in the relationship. This article aims to analyze and summarize research findings regarding the reasons for why women persist in violent dating relationships. This research uses literature study methods. Article searches were conducted through Google Scholar and Garuda with the keywords "kekerasan dalam pacaran", "dating violence", and "abusive relationships". The results of the study raised ten main themes about the reason why women stay in abusive dating relationships, namely: pessimistic feelings about new relationships, feeling trapped in dating violence, fulfilling affection needs, dependence on partners, positive expectations in relationships, positive views of partners, considering conflict in relationships to be normal, social influences, scared to talk about dating violence, and other factors such as religion, duration of relationship, and individual age.